On war - Clausewitz, Carl von, 1780-1831.; Howard, Michael, 1922-2019; Paret, Peter; Brodie, Bernard, 1910-1978 (Princeton, N.J. : Princeton University Press, 1976)
On War is the most significant attempt in Western history to understand war, both in its internal dynamics and as an instrument of policy. Since the work's first appearance in 1832, it has been read throughout the world, and has stimulated generations of soldiers, statesmen, and intellectuals. The most significant attempt in Western history to understand war, both in its internal dynamics and as an instrument of policy, Carl von Clausewitz's book stands as one of the world's great classic works on the subject.
Bk. 6. Defense -- Attack and Defense -- The Relationship between Attack and Defense in Tactics -- The Relationship between Attack and Defense in Strategy -- Convergence of Attack and Divergence of Defense -- The Character of Strategic Defense -- Scope of the Means of Defense -- Interaction between Attack and Defense -- Types of Resistance -- The Defensive Battle -- Fortresses -- Fortresses-Continued -- Defensive Positions -- Fortified Positions and Entrenched Camps -- Flank Positions -- Defensive Mountain Warfare -- Defensive Mountain Warfare-Continued -- Defensive Mountain Warfare-Concluded -- Defense of Rivers and Streams -- Defense of Rivers and Streams-Continued -- A. Defense of Swamps -- B. Inundations -- Defense of Forests -- The Cordon -- The Key to the Country -- Operations on a Flank -- Retreat to the Interior of the Country -- The People in Arms -- Defense of a Theater of Operations -- Defense of a Theater of Operations-Continued -- Defense of a Theater of Operations-Continued: Phased Resistance -- Defense of a Theater of Operations-Concluded: Where a Decision Is Not the Objective -- Bk. 7. The Attack -- Attack in Relation to Defense -- The Nature of Strategic Attack -- The Object of the Strategic Attack -- The Diminishing Force of the Attack -- The Culminating Point of the Attack -- Destruction of the Enemy's Forces -- The Offensive Battle -- River Crossings -- Attack on Defensive Positions -- Attack on Entrenched Camps -- Attack on a Mountainous Area -- Attack on Cordons -- Maneuver -- Attacks on Swamps, Flooded Areas, and Forests -- Attack on a Theater of War: Seeking a Decision -- Attack on a Theater of War: Not Seeking a Decision -- Attack on Fortresses -- Attack on Convoys -- Attack on an Enemy Army in Billets -- Diversions -- Invasion -- The Culminating Point of Victory -- Bk. 8. War Plans -- Introduction -- Absolute War and Real War -- A. Interdependence of the Elements of War -- B. Scale of the Military Objective and of the Effort To Be Made -- Closer Definition of the Military Objective: The Defeat of the Enemy -- Closer Definition of the Military Objective-Continued: Limited Aims -- A. The Effect of the Political Aim on the Military Objective -- B. War Is an Instrument of Policy -- The Limited Aim: Offensive War -- The Limited Aim: Defensive War -- The Plan of a War designed to Lead to the Total Defeat of the Enemy -- A Commentary -- A Guide to the Reading of On War / Bernard Brodie.
Includes bibliographical references.
"Prepared under the auspices of the Center of International Studies, Princeton University."
Translation of Vom Kriege.
Keywords: Military art and science; War; Military Science; Armed Conflicts; Military art and science; War